Dependencia al móvil y habilidades sociales en adolescentes de una unidad educativa de la ciudad de Loja, Periodo 2022 - Romero Romero, Jeleen Cristhina (2022)
The cell phone has allowed that relationships be strengthened and communication become instantaneous regardless of distance or space, which has had a great reception in people especially in adolescents, who have made a massive use of this device due to features and functions it offers. However, its excessive use led to a dependence on the device, which can lead to several negative consequences at personal, family and social level, especially in social skills that are important at this stage, which are expected to develop properly. In view of this situation, the investigation question presented is answered: what is the relationship between cell phone dependence and social skills in adolescents of Lauro Guerrero Military School? This study had a quantitative, nonexperimental, cross-sectional, descriptive-correlational approach in which 132 students participated. The instruments used for data collection were the Cell Phone Dependence Test and Goldstein's Social Skills Scale. The results obtained showed that most of the population presented a moderate level of cell phone dependence; for social skills, it was determined that a good level of social skills prevailed in most of the population. It was determined that there is no relationship between cell phone dependence and social skills through the elaboration of the cross table and as a complement, Kendal's Tau c statistical test was applied, which showed that a greater dependence on cell phones, the higher the social skills were not affected. Therefore, a promotion plan focused on Mental Health was developed to promote the correct use of cell phones and to enhance social skills in adolescents